Literasi Digital untuk Meningkatkan Pemahaman Siswa SMA Paskalis Jakarta Mengenai Etika Komunikasi di Media Sosial - Parlindungan, Davis Roganda; Haloho, Heppy New Year; Silvian, Vergio; Syabanera, Nasya Dochka; Cahyadi, Larissa Belva; Eugenia, Janice Florence; Pattymahu, Gracia Christabel Henrietta; Kusumawardani, Fadilla; Clarissa, Eleane Cyrilla; Fernando, Erick (Dharma Sevanam : Jurnal Pengabdian Masyarakat, 2023)
The presence of social media is a double-edged sword; on the one hand, it is very advantageous to the community as freely accessible public media and promotional media that is capable of creating user engagement and identifying people who are geographically separated. However, it has a negative impact as a communication medium because it contains harsh and inflammatory words or comments, does not respect others' privacy rights, spreads messages that contain discriminatory elements of SARA, and plagiarizes writing, pictures, or photos that protect copyright. Other undesirable behaviors include cybercrime, addictive behavior, the proliferation of pornography, fake news, hate speech, bullying, and negative global environmental impacts such as terrorism, radical teachings, narcotics, and hedonistic lifestyles. The adolescent age group is the most concerning to both perpetrators and victims. As a result, it is critical to understand the ethics of social media communication among adolescents through digital literacy, where the ability to use social media is not limited to knowledge but also stresses attitudes and ethical behavior in expressing ideas positively. This means that when communicating with people, messages must be conveyed with genuine intent and desires, patience, mutual respect, and empathy. The goal of this community service project is to improve the knowledge and communication ethics of adolescents when it comes to utilizing the digital world, particularly social media, with a focus on Paskalis High School students in Central Jakarta. According to the findings of the evaluation of the service activities for the participants, the majority offered pretty positive replies in which they gained insight into new information and understanding connected to digital literacy and social media communication ethics.